Perfect remains - Fields, Helen , 1969- (A D.I. Callanach thriller, 2017)
The first in a nail-shredding new crime series. On a remote Highland mountain, the body of Elaine Buxton is burning. All that will be left to identify the respected lawyer are her teeth and a fragment of clothing. In the concealed back room of a house in Edinburgh, the real Elaine Buxton screams into the darkness. Detective Inspector Beau Callanach has barely set foot in his new office when Elaine's missing persons case is escalated to a murder investigation. Having left behind a promising career at Interpol, he's eager to prove himself to his new team. But Edinburgh, he discovers, is a long way from Lyon, and Elaine's killer has covered his tracks with meticulous care. It's not long before another successful woman is abducted from her doorstep, and Callanach finds himself in a race against the clock. Or so he believes ...The real fate of the women will prove more twisted than he could have ever imagined